OPTIMASI DIAMETER POROS TERHADAP VARIASI DIAMETER SPROKET PADA RODA BELAKANG SEPEDA MOTOR - Daswin Basselo; Stenly Tangkuman; Michael Rembet (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2014)
The rear wheel shaft of a motorcycle is classified as an axle which is supporting the bearing so that the rear tire rotated well. This study is aimed to get the optimum diameter of shaft which is capable of withstanding the load in accordance with the existing load conditions, and analyzing the torque ratio between the front and rear sprocket which have varied diameter. Optimization modeling program is using Matlab 2010. Optimization is done by using objective variable function accompanied with constraints in terms of stress and deflection on the rear axle while supporting the loads. The results of Optimization are Do 14 mm and Di 12,0889 mm, 12,0817 mm, 12,0627 mm, 12,0597mm with factory standard power of motorcycle (8426,41 Nm/s) which is complying to optimization rules.Â The optimization result shows the decreasing ofÂ inner diameter of the shaft along with increasing the sprocketâ€™s diameter. Key word : Shaft, optimization, outer diameter (Do), inner diameter (Di).